Food – first, to do no harm (a review) - Mariola Chmielewska; Jerzy Tys; Jacek Petkowicz; Beata Petkowicz (Acta Agrophysica, 2018)
The paper addresses the problems of the effect of food on human health. It presents the chemical composition, the proportions of amino acids, fatty acids and saccharides in food products that we consume, and their effect on food quality and safety. It also presents the functions and criteria that should be met by food products, and the conditions in which they should be produced so that their consumption may be the least harmful to the organism. The paper presents also a classification of food products in conformance with the current definitions of functional food and nutraceuticals. Based on a literature review, it is demonstrated what chemical composition of food is particularly dangerous in the aspect of disorders of the cardiovascular system and neoplastic diseases. The paper addresses also the role of fatty acids and their impact on the development of various diseases. Also presented is the study on the oil “Kropla Zdrowia” that was conducted at the Institute of Agrophysics in the medical aspect.